Improved Weighted 0-1 Knapsack Method (WKM) to Optimize Resource Allocation - Alrawi , Maha A. Hammood; Ali , Israa Tahseen; Saied , Olaa Amer (Iraqi Journal of Science, 2022)
In this paper an improved weighted 0-1 knapsack method (WKM) is proposed to optimize the resource allocation process when the sum of items’ weight exceeds the knapsack total capacity .The improved method depends on a modified weight for each item to ensure the allocation of the required resources for all the involved items. The results of the improved WKM are compared to the traditional 0-1 Knapsack Problem (KP). The proposed method dominates on the other one in term of the total optimal solution value of the knapsack .